2023
DOI: 10.1002/aenm.202302552
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Defect Healing and Device Encapsulation via Structure Regulation by Silicone Polymer Enables Durable Inverted Perovskite Photovoltaics with High Efficiency

Tong Wang,
Zhi Wan,
Xin Min
et al.

Abstract: Polymers play a crucial role in promoting the progress of high‐performance inverted perovskite solar cells (PSCs). However, few polymers have simultaneously achieved defect passivation and device encapsulation in PSCs. Herein, a telechelic silicone polymer (poly(dimethylsiloxane‐co‐methylsiloxane acrylate) [PDMA]) is introduced, which possesses crosslinking capability to enable structure regulation through a condensation reaction. By leveraging the advantages of the polymers before and after crosslinking, a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Distinct additives such as methylamine formate (MAFa), an ionic liquid (IL) additive, mitigated octahedra distortion, suppressing the phase transition of α-FAPbI 3 to δ-FAPbI 3 [91]. Poly(dimethylsiloxane-co-methylsiloxane acrylate) improved the solubility and passivated defects [92], and potassium hexafluoroprop-ane-1,3-disulfonimide inhibited PbI 2 crystallization, adjusted crystal orientation, and passivated defects [93]. Pemirolast potassium considerably ameliorated carrier dynamics and mitigated residual stress [94].…”
Section: Management Of the Bulk Properties Of Pvk Filmsmentioning
confidence: 99%
“…Distinct additives such as methylamine formate (MAFa), an ionic liquid (IL) additive, mitigated octahedra distortion, suppressing the phase transition of α-FAPbI 3 to δ-FAPbI 3 [91]. Poly(dimethylsiloxane-co-methylsiloxane acrylate) improved the solubility and passivated defects [92], and potassium hexafluoroprop-ane-1,3-disulfonimide inhibited PbI 2 crystallization, adjusted crystal orientation, and passivated defects [93]. Pemirolast potassium considerably ameliorated carrier dynamics and mitigated residual stress [94].…”
Section: Management Of the Bulk Properties Of Pvk Filmsmentioning
confidence: 99%
“…To achieve desirable perovskite films, additive engineering is one of the most effective approaches to regulate perovskite grain size, passivate film defects, and modulate energy levels, thus improving the quality of perovskite films as well as the photovoltaic performance and stability of devices. Various types of additives have been utilized, including organic and inorganic cations such as MA + , Cs + , and K + , ,, anions such as −COOH , and −SCN, small molecules, and polymers that act as Lewis bases. It has been reported that amine additives play an active role in regulating perovskite grain sizes and passivating film defects. The introduced 2-fluoroethylamine into the PbI 2 precursor solution resulted in passivated film defects, suppressed nonradiative complexation, and extended carrier lifetime, obtaining a rigid device with a maximum efficiency of 23.40% .…”
Section: Introductionmentioning
confidence: 99%
“…The UV−vis absorption spectra in Figure 4c and the Tauc plot in Figure S16 present that the bandgap of the perovskite films retained constant with or without the presence of HEMA, while the target perovskite film displayed a higher absorption intensity than the control film, which was ascribed to the enlarged grain size and improved crystallinity aided by the HEMA. 46 When excited by a 532 nm laser at the same light intensity, the target films exhibited higher photoluminescence (PL) intensity in comparison to the control perovskite film, as seen in Figure S17, indicating a suppressed nonradiative recombination center in the target films. Time-resolved photoluminescence (TRPL) spectra in Figure 4d show that the target perovskite film presents a longer averaged carrier lifetime of 421.20 ns than the 278.85 ns of the control perovskite film.…”
mentioning
confidence: 99%
“…The perovskite crystallization is schematically illustrated in Figure . In particular, during the crystallization of pristine perovskite by using DMF and DMSO as solvent, crystal nucleation was favored for the formation of some intermediate adducts of DMSO–PbI 2 , which can act as a nucleus to seed perovskite crystallization, while the crystal growth process was retarded because extra energy is required to break the coordination of the adducts as well as to evaporate the DMSO from the film. , After the deposition of pristine perovskite, randomly oriented crystals start to grow with the volatilization of DMF and DMSO. On the contrary, the addition of HEMA into the precursor solution can generate a new type of adduct, i.e., FAI–PbI 2 –HEMA instead of PbI 2 –DMSO, which accelerated nucleation because of its enlarged size and enhanced association.…”
mentioning
confidence: 99%